Neonatal outcomes of elective caesarean section at term without prophylactic use of antenatal corticosteroids - Masheer, Shazia; Aziz Ali, Arzina; Jiwani, Uswa; Gheewala, Sakina; Jang, Jehanzaeb; Shaheen, Fariha; Rizvi, Arjumand; Memon, Pareesa; Ariff, Shabina (International Journal Of Community Medicine And Public Health, 2023)
Background: We aimed to describe the outcomes of neonates born at or near term to women undergoing elective C-section without prophylactic corticosteroids. Methods: Single-centre retrospective observational study of neonates born between 36+0 and 42+0 weeks. Associations between neonatal complications and maternal and neonatal factors were evaluated by univariate analyses and multivariate logistic regression. Results: A total of 2151 (26%) neonates were born by elective C-section during the study period, of whom 429 were included in the study. Fifty-six (13.05%) neonates developed some complication with 39 (9.1%) requiring NICU admission. Respiratory distress syndrome (RDS) and hypoglycemia occurred in 21 (4.9%) and 7 (1.6%) neonates, respectively. Maternal age >35 was associated with higher odds of neonatal complications (OR: 5.52, 95% CI: 1.02-29.74, p=0.047). Conclusions: The rate of RDS was comparable to other reported studies. The study revealed a high rate of term elective C-sections, providing grounds for conducting further research on administering antenatal corticosteroid to this population to reduce new-born morbidities.